Chronic liver disease and hepatic encephalopathy: Clinical profile and outcomes - Onyekwere, CA; Ogbera, AO; Hameed, L (Nigerian journal of clinical practice, 2011)
Hepatic encephalopathy (HE) is an important neuropsychiatry complication of liver disease causing significant morbidity and mortality worldwide. Efforts at improving the outcome have resulted in development of new strategies in the management given the background of new insights in the pathogenesis of this disease entity. Understanding the disease profile including precipitants as well as prognostic factors will contribute in this regard as new strategies are yet to be widely applied. The aim of this report is to document the profile of patients with HE, the precipitants, prognostic factors as well as the scope of the burden associated with it. In this prospective study, all patients managed for HE from January to December 2008 were recruited. A questionnaire was used to extract their basic demographics, clinical features noting any possible precipitants, complications, management protocol as well as outcome. A total of 21 subjects (11 females and 10 males) within the age range of 16-83 years were seen during the period under review. (mean age 57.9 ± 13). There was no significant difference in the mean ages of males and females. Two patients had acute encephalopathy, while others had acute-on chronic encephalopathy. The risk factors for liver disease included significant alcohol ingestion, hepatitis B virus infection, and previous jaundice, while other complications of liver disease noted were deepening jaundice, ascites, bleeding tendencies, and renal failure. The identified precipitants for HE were sepsis 6 (29%), electrolyte inbalance 3 (14%), gastrointestinal bleed 5 (24%), drugs (5%), and possible malignant transformation 6 (29%). Focus of sepsis was bacterial peritonitis in two cases. Majority of our patients (61%) came during advanced stage of liver disease (Child-Pugh class C). Length of hospital stay ranged from 1 to 7 weeks and a mortality of 48% was observed. Predictors of mortality were a history of significant alcohol ingestion, previous blood transfusion, Hepatitis B and C infections, and severe liver dysfunction on presentation (Child-Pugh class C). HE is associated with a high mortality rate and this scenario is associated with a history of previous blood transfusion, Hepatitis B and C infections, and severe liver dysfunction on presentation. Measures to reduce the burden of viral Hepatitis B and C, safe blood transfusion, and responsible use of alcohol should be promoted. Screening of those at risk of encephalopathy (liver disease patients) with a psychometric test of good predictability should be part of their routine evaluation in daily practice so as to detect cases of latent encephalopathy. Intensive care facilities and necessary personnel should be provided.